(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
Hypertension, or high blood pressure, in children was previously considered a rare condition, but with obesity and lifestyle changes among children and adolescents, the problem is becoming more widespread. This article highlights the important aspects of diagnosing hypertension in children.